A note on the literal meaning(s) of the term (ḍamīr al-)faṣl - Kasher, Almog (Journal for semitics, 2012)
This article follows the semantic shift which the literal sense of the term (ḍamīr al-)faṣl underwent in medieval Arabic grammatical tradition. Whereasearlier grammarians understood faṣl as meaning "separation", due to the "physical" property of the constituent in question being positioned between the subject and the predicate (or their counterparts), the term was later normally reinterpreted as "disambiguation", due to the constituent's function of disambiguating the syntactic function of the following constituent as a predicate (or its counterpart). This shift may have been either intentional or due to later grammarians' misinterpretation of earlier writings.